2014
DOI: 10.1136/bmj.g2696
|View full text |Cite
|
Sign up to set email alerts
|

Selecting an internationally diverse medical workforce

Abstract: Doing it with respect is in everyone’s best interests

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The virtue of standardised tools is that the assessment is the same for all candidates. Despite being validated, 3 however, the disadvantage of standardised assessment is its questionable relevance to real world clinical practice; it has been suggested that the “standardisation of final licensing, and fitness to practise examinations may make educationalists weep with joy, but there is no clear evidence that it makes for better doctors.” 4 Could we perhaps do better?…”
mentioning
confidence: 99%
“…The virtue of standardised tools is that the assessment is the same for all candidates. Despite being validated, 3 however, the disadvantage of standardised assessment is its questionable relevance to real world clinical practice; it has been suggested that the “standardisation of final licensing, and fitness to practise examinations may make educationalists weep with joy, but there is no clear evidence that it makes for better doctors.” 4 Could we perhaps do better?…”
mentioning
confidence: 99%
“…The virtue of standardised tools is that the assessment is similar for all candidates. Despite having been validated, 3 however, they do not assess proficiency in actual practice. The disadvantage of standardised assessment is its questionable relevance to real world clinical practice; it has been suggested that the “standardisation of final, licensing, and fitness to practise examinations may make educationalists weep with joy, but there is no clear evidence that it makes for better doctors.” 4 Could we perhaps do better?…”
mentioning
confidence: 99%
“…Given the growing demand for FTPs in the United States, there is a need to fairly select, train, and support this diverse group of international physicians. 33 Physicians in this study were evaluated on their performance using the PULSE 360 Survey and were compared across gender, country of training, native language, age, and board certi cation status. There were no signi cant differences in their reported performance on professionalism, teamwork, motivating behaviors, discouraging behaviors, technical practice style, or patient interactions.…”
Section: Discussionmentioning
confidence: 99%